Pengaruh Pelatihan Cuci Tangan Bersih dengan Metode Bermain Puzzle terhadap Kemampuan Melakukan Cuci Tangan Anak Tunagrahita di SDLB-C TPA Kabupaten Jember (The Effect of Hands Washing Training with Puzzle Method to Ability to Wash Hands of Children with - Yunus Nur Zakarya; Erti Ikhtiarini Dewi; Tantut Susanto (Pustaka Kesehatan, 2016)
Children with mental retardation are children who have a disruption to their intellegence level. Oneof the problem that occurs to them is their inability to perform hands washing. An attempt toimprove their ability is to give hands washing training with puzzle method. This study aimed toanalyze the effect of hands washing training with puzzle method to ability to wash hands ofchildren with mental retardation at SDLB-C TPA in Jember. Study design was a pre experimentalresearch with pretest-posttest group. The samples were 25 children with mental retardation. Dataanalysis used Wilcoxon Signed Rank Test. The result showed that there was an effect of handswashing training with puzzle method with ability to wash hands of children with mental retardationat SDLB-C TPA in Jember (p value <0.05). Recommendation of this study is the need of theschool to have hands washing facility such as an “emergency” wastafel, soap, and tissue paperprovided anytimeKeywords: Hand Washing, Mental Retardation, Puzzle